THE COURSE OF EXPERIMENTAL INFECTION OF THE CHICK EMBRYO WITH THE VIRUS OF EQUINE ENCEPHALOMYELITIS - Bang, Frederik B. (The Rockefeller University Press, 1943)
The titration curve for the virus of Eastern equine encephalomyelitis inoculated into the 10 day old chick embryo shows that the maximum increase in virus content continues until shortly before the generalized destruction of the embryo is apparent. This is followed by a stationary phase. Histological studies of infected embryos fail to demonstrate selective tissue destruction, and titrations show the virus to be distributed throughout the egg, although concentrated in the embryo. The chorioallantoic membrane gradually becomes increasingly resistant with age to both the Eastern and Western viruses. Increased resistance with age is also apparent in the hatched chick. These findings are based on the use of the chick embryo itself as the test animal to determine the 50 per cent mortality end-point. The limits of accuracy of this method are defined.